A memória documental sobre Mariazinha Penna, a santa popular de Santa Maria/RS - Ercolani, Marcelo Gabriel (2022)
Maria Zaira Cordova Penna, better known as Mariazinha Penna, having been affected by cancer, died in extreme suffering, still very young, only 20 years old, in 1953. Since then, according to reports, an intense pilgrimage to her tomb began, where many people come to pray, ask for intercession, give thanks, or simply out of curiosity, given the impact of their history of faith and resignation in the face of a painful illness. This research is justified by the popularity of Mariazinha, consolidated as a religious icon of Santa Maria/RS for almost 70 years, whose devotion falls within the concept of the intangible cultural heritage of the municipality, based on the definition elaborated by the United Nations Organization for Education, Science and Culture (UNESCO). For this reason, a research project was submitted to the Graduate Program in Cultural Heritage at the Federal University of Santa Maria (PPGPC/UFSM), in the Research Line of Archival Documental Heritage. Thus, since 2019, based on exploratory and qualitative research, documents, reports (participant research), and published texts on Mariazinha Penna, the saint of Santa Maria – as she is recognized by a portion of the local community – have been gathered and analyzed, taking as materiality the written media, especially the extinct Jornal A Razão, the internet, the biography, and other related publications. In addition, particularities were noted regarding the paraliturgical celebrations in honor of the saint, which systematically occur in the Municipal Ecumenical Cemetery and the Nossa Senhora da Glória Parish – the recitation of the Rosary to Mariazinha Penna –. Based on the documentation raised, we sought to compare and ratify information about the devotional phenomenon portrayed in the biography “Mariazinha Penna: a predestined”, work by Abelin (1988) designated as a parameter of this research. It was verified, therefore, that there was a correlation between the information present in the aforementioned book with the existing data in the documentary collection, corroborating and complementing information about Maria Zaira. But some possible inconsistencies between the sources were also noted. However, it can be deduced that Mariazinha is still present in the social imaginary of Santa Maria, considering that there are different memory resources associated with the venerated one, available in public and ecclesiastical archives, monuments, exvotos, prayers, means of communication, cemetery space, religious space, in addition to its diffusion through oral tradition. Finally, it is observed that other local characters were identified, who were subjected, at some point, to popular processes aimed at building devotions, most of which had a life story and/or tragic death as vectors of sacralization, namely, Conceição Carvalho de Vargas, Terezinha Baldaço (or Baldasso), Father Quedi, Silvia Regina Leal and Bernardo Uglione. These findings, it is intended to systematize research projects and subsequent comparative study.